2018
DOI: 10.1585/pfr.13.3406070
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Measurements of Metastable Atom Density and Electric Field Strength in a Microhollow Cathode Helium Plasma by Laser Absorption Spectroscopy

Abstract: We apply laser absorption spectroscopy to direct-current hollow-cathode helium plasma generated in a 0.3mm-diameter cylindrical hole at gas pressures of 10-80 kPa. The measured transitions are 2 3 S-2 3 P and 2 1 P-3 1 D. We evaluate the helium metastable 2 3 S density and gas temperature using the former transition and the 2 1 P atom density and electric field strength from the latter one. The observed lateral distributions of the 2 3 S and 2 1 P atom densities depend on the gas pressure, which results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…At 20-60 kPa, both n 23S and n 21P are locally high in the vicinity of the cathode-wall. In our previous results at the cathode-hole diameter of 0.3 mm, and at 10-80 kPa, 27) it is found that a hole appears in the structure of n 23S and n 21P near the center at high pressures and this may be due to the shrinking sheath length. This is consistent with the present results at the cathode-hole diameter of 1.0 mm.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…At 20-60 kPa, both n 23S and n 21P are locally high in the vicinity of the cathode-wall. In our previous results at the cathode-hole diameter of 0.3 mm, and at 10-80 kPa, 27) it is found that a hole appears in the structure of n 23S and n 21P near the center at high pressures and this may be due to the shrinking sheath length. This is consistent with the present results at the cathode-hole diameter of 1.0 mm.…”
Section: Resultsmentioning
confidence: 77%
“…The values are roughly a factor 5-10 lower than those of the results at the cathode-hole diameter of 0.3 mm. 22,27) At 5 kPa and 10 kPa, both n 23S and n 21P exhibit peaks at the center. At 20-60 kPa, both n 23S and n 21P are locally high in the vicinity of the cathode-wall.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations